2021
DOI: 10.1103/physrevb.103.214113
|View full text |Cite
|
Sign up to set email alerts
|

Probing the nucleation of iron in Earth's core using molecular dynamics simulations of supercooled liquids

Abstract: Classical nucleation theory describes the formation of the first solids from supercooled liquids and predicts an average waiting time for a system to freeze as it is cooled below the melting temperature. For systems at low to moderate undercooling, waiting times are too long for freezing to be observed via simulation. Here a system can be described by estimated thermodynamic properties, or by extrapolation from practical conditions where thermodynamic properties can be fit directly to simulations. In the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 26 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…To frame these calculations at relevant pressure and temperatures, equations of state and melting curves must also be calculated for these models. We use the methodology of Wilson et al (2021) expanded to binary systems to identify nuclei, calculate nucleation rates and predict waiting times for systems to freeze.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To frame these calculations at relevant pressure and temperatures, equations of state and melting curves must also be calculated for these models. We use the methodology of Wilson et al (2021) expanded to binary systems to identify nuclei, calculate nucleation rates and predict waiting times for systems to freeze.…”
Section: Methodsmentioning
confidence: 99%
“…Both approaches, find that these simple systems reproduce the original prediction of Huguet et al (2018) with a 675 -807 K supercooling requirement for spontaneous homogeneous nucleation of the inner core. A metadynamic approach shows that metastable iron phases may lower the nucleation barrier in a two-step nucleation process (Sun et al, 2022) but much of this reduction is owed to a lower melting temperature and this metastable phase has not been reported in molecular dynamic studies of the same systems (Davies et al, 2019;Wilson et al, 2021). A recent laser driven shock experiment study on the melting curve of iron has suggested that the paradox does not exist and that the nucleation barrier is far lower than previously thought for planetary interiors (Kraus et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations